PERESEPAN OBAT COVID-19 DI INSTALASI FARMASI RAWAT JALAN RSAU DR.ESNAWAN ANTARIKSA PADA MASA PANDEMI BULAN JANUARI 2022 - Fitri Savitri; Yudha Sukowati; Syafrita Greacia (Jurnal Farmasi IKIFA, 2023)
WHO (World Health Organization) stated that covid-19 was a global pandemic on March 11, 2020. This virus has a rapid rate of development and spread with a high infection rate. According to national covid-19 data in January 2022, it shows that the most covid-19 patients were on January 31, 2022 with data on patients in treatment or self-isolation as many as 68,596. The provinces with the most cases in 2022 in January 2022 are DKI Jakarta Province as much as 20.6%, West Java 18.3%, Central Java 10.3% and East Java 9.5%. The purpose of this study was to determine the description of outpatient drug prescribing during the covid-19 pandemic at the Air Force Hospital dr.Esnawan Antariksa. This study uses a quantitative descriptive method. The sample in this study was 164 covid-19 prescription sheets. The results of this study showed that there were 112 prescriptions containing antibiotics and 164 prescriptions containing vitamins. The conclusion of this study is that the prescription for covid-19 drugs is vitamin C 1,685 drugs (19.03%), vitamin D 1,148 drugs (12.97%), paracetmol 1,570 drugs (17.73%), zinc 1,100 drugs (12.43%), acetylcysteine 2,350 drugs (26.54%), azithromycin 560 drugs (6.33%), and the lowest was favipiravir with 440 drugs (4.97%).